Lapsen etu oikeuslähteenä erityisesti riita- ja hakemusasioissa - Mustasaari, Sanna; Tolonen, Hannele (Lakimies, 2024)
Best interests of the child as a source of law According to Article 3 of the UN Convention on the Rights of the Child (CRC), in all actions concerning children, whether undertaken by public or private social welfare institutions, courts of law, administrative authorities or legislative bodies, the best interests of the child shall be a primary consideration. In this article, we examine the concept of the best interests of the child, from the perspective of recent theoretical discussions on children’s rights and from the perspective of the Finnish legislation and case law. We specifically ask what it means to say that an action concerns a child. Traditionally, discussions about the best interests of the child as a decision-making principle have focused on the child’s position in the family and matters directly affecting the child, such as custody disputes. The discourse on children’s rights and child law has strongly emphasised the broad principle of the best interests of the child extending to all actions of the authorities, as outlined in the CRC. We explore how the best interests of the child is taken into account as a norm that determines the decision that will be reached, and how the scope of matters in which the best interests of the child are the most central decision-making criterion might be defined. The best interests of the child -norm has recently emerged in case law in interesting ways, for example, in a decision by the Supreme Court of Sweden concerning enforcement, where the best interests of the child prevented the seizure of a residential property due to a parent’s debt. In this article, we observe the use of the norm of the primacy of the best interests of the child and consider its possibilities in legal argumentation in various other types of matters, especially in different fields of civil law.